2016
DOI: 10.6007/ijarafms/v6-i3/2172
|View full text |Cite
|
Sign up to set email alerts
|

To Assess the Impact of Social Media Marketing on Consumer Perception

Abstract: As the fast growing adoption of social media technology, provide the different new ways of marketing a product. Now internet as well as social media has taken the status of backbone of every firm growth and this technology changed the way of doing businesses. It's essential for every firm to adopt this technology to advertise its products. In this research we assess the impact of social media marketing on consumer perception towards buying a product or making a decision to buy a product. With social media mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…patronage and loyalty). The usage of a model like this is not uncommon as Ali et al (2016), Chen (2014) and Mustapha et al (2017) used similar model (i.e. multiple regression analysis) in their studies.…”
Section: Methodsmentioning
confidence: 99%
“…patronage and loyalty). The usage of a model like this is not uncommon as Ali et al (2016), Chen (2014) and Mustapha et al (2017) used similar model (i.e. multiple regression analysis) in their studies.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in a related study, Alam and Khan (2015) also discovered that social media have a significant impact on brand awareness. Ali et al (2016) also discovered that social media marketing affects consumer perception and purchase decisions. In another related study by Abzari et al (2014), it was revealed that social media influenced consumer brand attitude and intention to buy from Khodro Company in Iran.…”
Section: Effects Of Social Media On Consumer Brand Awareness and Patronagementioning
confidence: 99%
“…Moving to the second are of our conceptual framework, i.e., the employment of social networks in building retail consumer loyalty, we have to admit that literature in the field covers quite broad spectrum of issues -from the role of consumer references and the rewarding engagement strategies, from the electronic word of mouth (e-WOM) and creation of online communities to the online communication strategies (Ali, 2016;Leonardi et al, 2013;Poturak & Softić, 2019;Pütter, 2017;Schivinski & Dabrowski, 2014). Thus, L. M. Rehnen and others (2017) and L.M.…”
Section: Figurementioning
confidence: 99%